Menguji Konsistensi Korelasi Job Satisfaction dengan Intensi Turnover: Studi Meta-Analisis - Ferdinand - Hindiarto (Buletin Psikologi, 2017)
This study examined the correlation between job satisfaction and turnover intention derived from various studies in 2009-2016 using meta-analysis method. The used samples consisted of 25 studies from 21 research journal drawn from online databases. Analyses were conducted using two artifacts, correction on error sampling and on error measures. Results of the study showed that correlation between job satisfaction and turnover intention in the 1st artifact was -0,46 and in the 2nd artifact was -0,56.